Polycystic Kidney Disease in Children: The Current Status and the Next Horizon - Cadnapaphornchai, Melissa A; Dell, Katherine M; Gimpel, Charlotte; Guay-Woodford, Lisa M; Gulati, Ashima; Hartung, Erum A; Liebau, Max C; Mallett, Andrew J; Marlais, Matko; Mekahli, Djalila; Piccirilli, Alixandra; Seeman, Tomas; et al. (American journal of kidney diseases, 2025)
Autosomal dominant polycystic kidney disease (ADPKD) and autosomal recessive polycystic kidney disease (ARPKD) are inherited disorders that share many features such as kidney cysts, hypertension, urinary concentrating defects, and progressive chronic kidney disease. The underlying pathogenic mechanisms for both include cilia dysfunction and dysregulated intracellular signaling. ADPKD has been traditionally regarded as an adult-onset disease whereas ARPKD has been classically described as an infantile or childhood condition. However, clinicians must recognize that both disorders can present across all age groups, ranging from fetal life and infancy to childhood and adolescence as well as adulthood. Here we highlight the points of overlap and distinct features for these disorders with respect to pathogenesis, diagnostic modalities (radiological and genetic), clinical assessment, and early therapeutic management. In particular, we consider key issues at 2 critical points for transition of care: fetal life to infancy and adolescence to adulthood. These time points are poorly covered in the extant literature. Therefore, we recommend guiding principles for transitions of clinical care at these critical junctures in the life span. Although there is no cure for polycystic kidney disease (PKD), recent insights into pathogenic mechanisms have identified promising therapeutic targets that are currently being evaluated in a growing portfolio of clinical trials. We summarize the key findings from these largely adult-based trials and discuss the implications for designing child-focused studies. Finally, we look forward to the next horizon for childhood PKD, highlighting gaps in our current knowledge and discussing future directions and strategies to attenuate the full burden of disease for children affected with PKD.
Keywords: Childhood polycystic kidney disease; Humans; dítě; Child; polycystické ledviny autozomálně dominantní; Polycystic Kidney, Autosomal Dominant; Adolescent; mladiství; genetics; pediatric clinical trials; polycystické ledviny autozomálně recesivní; Polycystic Kidney, Autosomal Recessive; lidé; transition of care